Energy cataract surgery in the St. Petersburg branch of the S. Fyodorov Eye Microsurgery State Institution: analysis of 27-year experience - E.V. Boiko; M.N. Nemsitsveridze; S.V. Shukhaev; E.A. Simak (Офтальмохирургия)
Purpose. Based on a comparative analysis of the results of using various laser methods of cataract treatment in the process of developing energy surgery in the St. Petersburg branch The S. Fyodorov Eye Microsurgery Federal State Institution, to determine the advantages and disadvantages of the technologies used. Material and methods. Analysis of the results of laser cataract extraction, ultrasonic phacoemulsification and combined surgery is based on data from a study of 28 802 surgical interventions (Phacoemulsification (Phaco) – 15 520, laser cataract extraction (LCE) – 7945, FemtoPhaco – 5135, FemtoLCE – 202) performed over the period 1995–2022. Results. The operative complication rate was 0.6, 0.55, 0.5 and 0% for Phaco, LCE, FemtoPhaco and FemtoLCE respectively. Visual acuity after LCE and FemtoLCE >0.8 was observed in more than 70% of cases, and in other groups such a functional result was achieved in 57% of cases. Comparing the postoperative spherical equivalent, a significant difference was noted only between the FemtoPhaco and standard Phaco (p=0.03), and between FemtoLCE and LCE groups (p=0.01), it indicates the advantage of femtolaser support for cataract surgery getting in target refraction. Analysis of endothelial cells loss reflects a significant advantage in groups with femtolaser support (p=0.01; p=0.02), as well as in the group of LCE and FemtoLCE over standard Phaco (p=0.01; p=0.02, respectively). Conclusion. Laser cataract extraction is an effective and safe technology that can be compared to ultrasonic phacoemulsification. The use of femtosecond laser assistance provides significantly lower deviation from the planned postoperative refraction. Modern laser technologies are safe and can reduce the risk of endothelial loss more effectively than standard Phaco.